Oxytocin effects on osteoblastic differentiation of Bone Marrow Mesenchymal Stem Cells from adult and aging female Wistar rats - Santos, Leandro Figueiredo [UNESP]; Singulani, Monique Patricio [UNESP]; Stringhetta-Garcia, Camila Tami [UNESP]; Oliveira, Sandra Helena Penha de [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Dornelles, Rita Cássia Menegati [UNESP] (Elsevier, 2018)
Recently, it has been suggested that oxytocin (OT) might play a role in the control of bone remodeling and in bone health of young and adult females. The purpose of this study was to evaluate the effect of osteogenic medium (OM) plus OT (OM + OT; 100 nmol/L) on osteoblastic differentiation of bone marrow mesenchymal stem cells (BMMSCs) from cyclic adult (12 months old) and acyclic aging (24 months old) female Wistar rats. After 14 days, OM + OT increased the oxytocin and oxytocin receptor in the BMMSCs from animals of both age groups relative to OM controls. Alkaline phosphatase activity was higher in the OM + OT than OM group in BMMSCs from 24-month-old female rats. OM + OT improved osteogenic differentiation, observed by anticipated mineralization and increased gene expression of bone morphogenetic protein 2, bone sialoprotein, osteopontin and osteocalcin in both aged relative to OM controls. These findings suggest a role for OT as an adjuvant to induce osteoblastic differentiation of BMMSCs from aged female rat.
Keywords: Aging; Bone marrow; Osteoblast; Oxytocin; Rat